2019
DOI: 10.12688/f1000research.19327.1
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of antigen-specific IgY on pyocyanin-treated human lymphoma Raji cells

Abstract: Background: Pyocyanin (PCN), a highly pathogenic pigment produced by Pseudomonas aeruginosa, induces caspase 3-dependent human B cell (Raji cells) death. The aim of the present study, therefore, was to assess whether antigen-specific IgY antibodies may be protective on PCN-induced Raji cell death. Methods: Chickens were subcutaneously immunized with Freund's complete adjuvant containing PCN, and then given two boosted immunizations.  Anti-PCN IgY antibodies were purified from egg yolk and detected using an aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Pyocyanin is a small-molecule toxin that is easily able to cross cell membranes usually through a T2SS quorum-sensing dependent mechanism. Pyocyanin is a redox-active tricyclic zwitterion shown to affect the respiratory, cardiovascular, urological, and central nervous systems by inducing oxidative stress within cells [ 111 , 112 ]. Pyocyanin directly oxidizes and depletes reduced glutathione, effectively neutralizing one of the major redox pathways.…”
Section: Description Of Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyocyanin is a small-molecule toxin that is easily able to cross cell membranes usually through a T2SS quorum-sensing dependent mechanism. Pyocyanin is a redox-active tricyclic zwitterion shown to affect the respiratory, cardiovascular, urological, and central nervous systems by inducing oxidative stress within cells [ 111 , 112 ]. Pyocyanin directly oxidizes and depletes reduced glutathione, effectively neutralizing one of the major redox pathways.…”
Section: Description Of Targetsmentioning
confidence: 99%
“…Due to this cascade, pyocyanin released by P. aeruginosa is especially toxic to cystic fibrosis patients, potentially due to its ability to induce neutrophil extracellular traps (NETs), which are able to exacerbate airway inflammation for their own benefit [ 113 ]. Thus, pyocyanin is a powerful mediator of cell injury used by P. aeruginosa and is a prime target to halt disease [ 112 ]. In fact, in vitro studies have demonstrated that anti-pyocyanin antibodies can provide protection [ 114 ].…”
Section: Description Of Targetsmentioning
confidence: 99%